Mutagen-induced alterations in the nucleic acid content and mitotic index of dugesia bengalensis kawakatsu - Aditya, A. K.; Chattopadhyay, Sanjib; Mitra, Shyamal; Kar, Suprakash (2002)
The effects of sublethal dose of 5-Bromouracil (5-BrU),2-Thiouracil (2-ThU), Dimethyl Sulphate (DMS) and ethy urethane (Ur) on DNA & RNA content, RNA/DNA ratio and mitotic indices of the entire dugesia bengalensis have been shown. Quantitative estimations of DNAs and RNAs were performed on total homogenates. DNA and RNA synthesis increased in 5-BrU and 2-ThU treated individuals, whereas decreasing trends were noted in DMS and Ur-treated planarians at 24h to 96h exposure. The increase mitosis in case with 5-BrU ansd 2-ThU and inhibition of mitosis in DMS and Ur treated cases (Aditya et al., 1994) has a direct corelation with the nucleic acid content and mitotic index in treated planarians.